Assessment of financial control system in Nifa Senior High School in North Akuapem Municipality in the Eastern Region Of Ghana - Asamoah, Samuel (2016)
A thesis submitted to the Department of Economics Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Science Economics,